Pamona Language Reduplication - Idris, Idris; Suputra, Gusti Ketut Alit; Ali, Ali; Uwu, Charles Reinaldo (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This qualitative research aims to describe the form and the meaning of Pamona Language Reduplication. Data collection techniques were carried out through listening method and conversational method, using the listening-engagement technique, the free-talk listening technique, the documentation technique and the note-taking technique. The research was conducted in Tiu Village, East Pamona District, Poso Regency. The data obtained were in the form of written and oral data obtained through data collection techniques. Furthermore, the data were analyzed through equivalent distribution. The result shows that the form and the meaning ofÂ  Pamona language reduplication are: (1) Reduplication of all words, (2) Partial reduplication, (3) Reduplication combined with affixes from the results of research that found the meaning of Pamona language reduplication, namely: (1 ) Stating the meaning of each other, (2) Stating the meaning of actions done repeatedly, (3) Stating the meaning of actions that are carried out without purpose, it is casual or it is just for fun.